Julio, Teresa. Maria Carratalà: música, escriptura i traducció - Keren Manzano (Quaderns)
Julio, Teresa Maria Carratalà: música, escriptura i traducció Lleida: Punctum, 2021, 244 p. ISBN 978-84-123303-5-9